Differences in the preparatory phase of mawashi geri jodan in karate - Pecoraioli, F.; Merni, F. (World Congress of Performance Analysis of Sport VIII, 2008)
For each execution model of the kick, the body is set in difference manner already before the take-off of the kicking foot. Hip action and the kicking foot orientation seems to be typical aspect of the technique. Differences in the preparatory phase could be due to the different learning model used in the two clubs and bring about two different trajectories of the striking foot during the rising phase. Trainer should pay attention to starting posture either during the teaching session or in case of technique mofication. So, before changing the rising phase technique of the kick, the teacher should modify previously the preparatory phase especially in the STR position (figures a, b).